Study on Design and Analysis of Ga2O3 Power MOSFETs with Source-field-plated - H. Fardi (New Approaches in Engineering Research Vol. 16, 2021)
This paper reports on the design and simulation of source-field-plated Ga2O3 power MOSFETs, investigating breakdown voltage, interface oxide charges and its relationship with the threshold voltage. For the device structure modeled a threshold voltage of -50 V is extracted. This value is comparable to the published experimental results with a similar device structure and physical parameters where an interface oxide charge density of 5 x1013 /cm2 is assumed in simulation. Simulation results indicate a breakdown voltage of 600 V and Ron resistance of 40 W-mm for Ga2O3 n-MOSFETs when a channel doping density of 1.5 x 1016 cm-3 is used. These results are in agreements with measured value of electric field breakdown and Ron resistance reported by others.